Potential determinants of unfavourable healthcare utilisation trajectories during the last year of life of people with incident Alzheimer Disease or Related Syndromes: a nationwide cohort study using administrative data. (30th March 2022) - Elyn, Antoine; Gardette, Virginie; Renoux, Axel; Sourdet, Sandrine; Nourhashemi, Fati; Sanou, Brigitte; Dutech, Michel; Muller, Philippe; Gallini, Adeline
Abstract: Background: people approaching the end-of-life frequently face inappropriate care. With Alzheimer Disease or Related Syndromes (ADRS), end-of-life is characterised by progressive decline, but this period remains difficult to identify. This leads to a lack of anticipation and sometimes with unfavourable healthcare utilisation trajectories (HUTs). Objective: to quantify unfavourable HUTs during the last year of life and identify their potential determinants in both community and nursing-home settings. Design: nationwide cohort study using administrative database. Setting: French community and nursing-home residents. Subjects: incident ADRS people identified in 2012, who died up to 31 December 2017. Methods: we used multidimensional clustering to identify 15 clusters of HUTs, using 11 longitudinal healthcare dimensions during the last year of life. Clusters were qualitatively assessed by pluri-disciplinary experts as favourable or unfavourable HUTs. Individual and contextual potential determinants of unfavourable HUTs were studied by setting using logistic random-effect regression models. Results: 62, 243 individuals died before 31 December 2017; 46.8% faced unfavourable end-of-life HUTs: 55.2% in the community and 31.8% in nursing-homes. Individual potential determinants were identified: younger age, male gender, ADRS identification through hospitalisation, shorter survival, life-limiting comorbidities, psychiatric disorders, acute hospitalisations and polypharmacy. In the community, deprivation and autonomy were identified as potential determinants. Contextual potential determinants raised mostly in the community, such as low nurse or physiotherapist accessibilities. Conclusions: Nearly half of people with ADRS faced unfavourable HUTs during their last year of life. Individual potential determinants should help anticipate advance care planning and palliative care needs assessment. Contextual potential determinants suggest geographical disparities and health inequalities. Graphical Abstract: